Digital Vulnerability and Public Response to Sextortion in Muslim Urban Society - Ria Hayatunnur Taqwa; Pilga Ayong Sari; Raziki Waldan (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
The rapid development of digital technology in urban Muslim societies creates new opportunities for education and social participation, but it also increases vulnerability to cybercrime, particularly sextortion. This crime threatens personal privacy and contradicts Islamic cultural and religious values, especially the principle of ḥifẓ al-‘irḍ (protection of honour). This study examines digital vulnerability and public responses to sextortion cases in Pontianak City, as well as the role of Islamic values in shaping awareness, prevention, and victim support. Using a mixed-methods approach, the research combined a survey of 120 respondents with in-depth interviews involving five key informants, including victims, digital activists, law enforcement officers, educators, and religious leaders. Quantitative data were analysed using descriptive statistics and logistic regression, while qualitative data were examined through thematic analysis. The findings show that 62.5% of respondents were aware of sextortion cases, but only 18.4% were willing to report them. Trust in law enforcement was low (22.5%), and most respondents had a medium level of digital literacy (48.3%). Regression analysis revealed that individuals with high digital literacy were 2.4 times more likely to actively support victims. Qualitative findings indicate that stigma, shame, and fear of religious consequences discourage reporting, while law enforcement faces technical barriers. Educators highlighted digital literacy as prevention, and religious leaders reframed sextortion through maqāṣid al-sharī‘ah, emphasising victim protection. The study concludes that addressing sextortion requires integrated digital education, empathetic religious discourse, and stronger institutional capacity.